Mainstreaming Biodiversity in Production Landscapes - Petersen, Caroline; Huntley, Brian (Washington, DC : Global Environment Facility, 2012)
This volume contributes to broadening the understanding and application of the concept of mainstreaming biodiversity. It captures the inputs to, and findings of an international workshop held in Cape Town, South Africa, in September 2004 on Mainstreaming Biodiversity in Production Landscapes and Sectors. The aims of the workshop were to: determine an operational definition of the concept of mainstreaming biodiversity in production landscapes and sectors; demonstrate the role of mainstreaming in advancing Convention on Biological Diversity (CBD) goals and Strategic Priority of the Global Environment Facility (GEF) work program; explore the scale at which mainstreaming can most effectively be implemented; critique successes and failures in achieving mainstreaming outcomes to date; and, brainstorm on modified or new approaches and tools. These aims are addressed in the first paper in this volume, which explores what is meant by "mainstreaming biodiversity," while the new approaches and tools-the products of the workshop-are outlined in the final paper, on guidelines for effective intervention. The remaining papers, presented at the open symposium preceding the workshop, represent a broad range of mainstreaming initiatives-in Africa, Asia, Australia, Europe, and Latin America, and in a large number of production sectors. A final paper, drafted by the Cape Town workshop participants, provides guidelines on effective interventions in achieving mainstreaming outcomes.